Building-based Decision-making: A Shared Planning Model for Inclusive Schools - Michael P. Brady; Charles R. Campbell; Patti C. Campbell (Educational Considerations, 1998)
When given support and the opportunity to work in building-based planning teams, teachers can implement remarkable school reforms.